(untitled) (Research, Society and Development, 2022)
With the growth of the population and the increase in demand for energy, the need arises for the development of alternative sources of generation. Biomethane obtained from biogas purification, which can be extracted from the decomposition of municipal solid waste, present in abundant quantities in many Brazilian cities, has emerged as an interesting alternative to complement the use of gases for combustion. Since the main fuel used today is natural gas, of fossil origin and with negative environmental impacts in its extraction, this article promotes an analysis of the energy and environmental viability of the use of biomethane for injection in the natural gas network, the computational tools. The results obtained indicate that the gas emissions from the combustion of natural gas and biomethane are practically equivalent and the difference in the flame temperature values between the fuels is around 7.1%. Thus, the insertion of biomethane in the natural gas network, besides not implying the increase of environmental impacts also does not promote significant losses in the energetic characteristics of the mixture.